A case of cerebral sparganosis in South America - Alejandro M. E. Boero; Pedro Garaguso; Jorge Navarré (Arquivos de Neuro-Psiquiatria)
Cerebral sparganosis (CS) is a parasitic infection caused by the larva of Spirometry mansonoides. Rarely it can affect the human brain. We report the case of a 24-year old man from Paraguay who suffered from seizures and headache for one. year. A frontal tumor was diagnosed by CT-scan and was subsequently resected. The pathological examination revealed a larva with Sparganum characteristics. The evolution of the patient was satisfactory. As far as we know, this is the first case of CS reported in South-America.